Novel super-soft PI composite adhesive tape and preparation method thereof

By using high-flex polyurethane acrylate in PI tape to blend with hydroxyl-containing polyimide, and adding nanosilicon dioxide and modified graphene oxide, the problem of insufficient flexibility of PI tape is solved, achieving higher flexibility and durability while maintaining good high temperature resistance.

CN119823657APending Publication Date: 2025-04-15江苏伊诺尔新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510078152.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Due to its high rigidity, existing PI tapes are less flexible, and cracks are prone to occur after multiple bends during use, resulting in a decrease in reliability and durability of electronic components.

Method used

High-flex polyurethane acrylate is blended with hydroxyl-containing polyimide, and nanosilicon dioxide and modified graphene oxide are added to form an ultra-soft PI composite tape. Through the combination and treatment of these materials, the flexibility and mechanical properties of the tape are improved while enhancing its bonding strength to the adhesive layer.

Benefits of technology

It improves the flexibility and durability of PI composite tape, so that it can be bent multiple times without breaking, greatly reducing the brittle breaking rate, and maintaining good high temperature resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of flexible electronic packaging materials, and particularly discloses a super-soft novel PI composite adhesive tape and a preparation method thereof. The super-soft novel PI composite adhesive tape comprises a base layer and an adhesive layer, the base layer comprises the following raw materials in parts by weight: 67-85 parts of hydroxyl-containing polyimide, 15-26 parts of high-soft polyurethane acrylate, 5-8 parts of nano silicon dioxide and 1-4 parts of modified graphene oxide, and the adhesive layer is an acrylic adhesive; in addition, the preparation method has the advantage of improving the flexibility and durability of the PI adhesive tape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of flexible electronic packaging materials, and more specifically, to a new type of ultra-soft PI composite tape and a preparation method thereof. Background Art

[0002] As electronic products develop towards thinner, lighter and more flexible, the demand for high-performance, ultra-soft packaging materials is increasing. Currently, the common polyimide tape on the market, namely PI tape, is widely used in flexible circuit boards and soft-pack batteries due to its good electrical insulation performance and thermal stability, and is often used as an insulating layer or protective layer.

[0003] The existing PI tape has high rigidity and low flexibility. If it needs to be bent multiple times during use, its service life is short and it is prone to cracks after multiple bending, which reduces the reliability of electronic components. This reduces the protection and isolation effect of the PI tape on electronic components and reduces its durability. Summary of the invention

[0004] In order to improve the flexibility and durability of PI tape, the present application provides a new type of ultra-soft PI composite tape and a preparation method thereof.

[0005] In the first aspect, the present application provides a new type of ultra-soft PI composite tape, which adopts the following technical solution: A new type of ultra-soft PI composite tape comprises a base layer and an adhesive layer. The base layer comprises the following raw materials in parts by weight: 67-85 parts of hydroxyl-containing polyimide, 15-26 parts of highly flexible polyurethane acrylate, 5-8 parts of nano silicon dioxide, and 1-4 parts of modified graphene oxide. The adhesive layer is an acrylic adhesive.

[0006] By adopting the above technical scheme, after high-flexibility polyurethane acrylate and polyimide are blended, the flexibility of the substrate can be effectively improved, thereby improving the flexibility of the PI composite tape, and the addition of nano-silica and modified graphene oxide can improve the mechanical strength of the base layer, so that the PI composite tape has good flexibility while its mechanical properties are not affected. The adhesive layer uses acrylic adhesive, and the hydroxyl group introduced in polyimide has high activity and can be cross-linked with acrylic adhesive and high-flexibility polyurethane acrylate, thereby improving the bonding strength between the base layer and the adhesive layer. At the same time, the addition of nano-silica and modified graphene oxide can improve the high temperature resistance of the PI tape, so that the PI composite tape has good heat resistance.

[0007] Preferably, the modified graphene oxide is graphene oxide covalently grafted with diisocyanate.

[0008] By adopting the above technical scheme, after the diisocyanate is covalently grafted, the isocyanate functional group can undergo a cross-linking reaction with the polyurethane, thereby improving the binding property between the modified graphene oxide and the highly flexible polyurethane acrylate, and enabling the graphene oxide to be better dispersed and bonded with the polyimide and the highly flexible polyurethane acrylate, thereby effectively improving the mechanical properties of the composite tape.

[0009] Preferably, the preparation method of diisocyanate covalently grafted graphene oxide comprises the following steps: ultrasonically dispersing graphene oxide in N,N-dimethylformamide to obtain a graphene oxide suspension, mixing 4'4-diphenylmethane diisocyanate and N,N-dimethylformamide and heating to 55°C with magnetic stirring, then dropwise adding the graphene oxide suspension and dibutyltin dilaurate, reacting at 55°C for 8-9h, centrifuging, washing, and drying at 50-55°C for 4-5h to obtain diisocyanate covalently grafted graphene oxide.

[0010] By adopting the above technical solution, diisocyanate can be successfully grafted onto the surface of graphene oxide, so that graphene oxide has isocyanate functional groups, thereby improving the degree of bonding between modified graphene oxide and highly flexible polyurethane acrylate, and at the same time helping to improve the dispersibility of modified graphene oxide.

[0011] Preferably, the mass ratio of the graphene oxide to 4'4-diphenylmethane diisocyanate is (0.12-0.24):(7.69-8.26).

[0012] By adopting the above technical solution and controlling the mass ratio of graphene oxide to 4'4-diphenylmethane diisocyanate, the grafting of diisocyanate on the surface of graphene oxide can be effectively regulated, thereby controlling the content of isocyanate functional groups on the surface of modified graphene oxide.

[0013] Preferably, the modified graphene oxide is further treated as follows: dissolving styrene in anhydrous ethanol by stirring, adding the modified graphene oxide and ultrasonically fractionating, adding benzoyl peroxide, heating in a water bath at 50-55° C. and stirring for 8-10 min, reacting at 80-85° C. for 5.5-6 h, cooling to room temperature, centrifuging, separating, washing with toluene, and vacuum drying.

[0014] By adopting the above technical solution, the modified graphene oxide is subjected to styrene graft polymerization treatment, thereby effectively improving the dispersibility of the modified graphene oxide during mixing and reducing agglomeration.

[0015] Preferably, before the modified graphene oxide is dispersed in the anhydrous ethanol solution of styrene, it is further subjected to the following treatment: ultrasonically dispersing the modified graphene oxide in water to obtain a modified graphene oxide suspension, stirring and dissolving a silane coupling agent in anhydrous ethanol, adding the modified graphene oxide suspension and ultrasonically dispersing the silane coupling agent, adjusting the pH to 4-5, heating to 50-55° C. and reacting for 3-3.5 hours, heating to 70-75° C. and reacting for 3-3.5 hours, cooling to room temperature, centrifuging, separating, washing with anhydrous ethanol, and vacuum drying.

[0016] By adopting the above technical solution, after the modified graphene oxide is first treated with a silane coupling agent, the grafting polymerization effect of styrene on the surface of the modified graphene oxide is better, further improving the dispersibility of the modified graphene oxide.

[0017] Preferably, the nano-silica is treated as follows: a silane coupling agent is added to toluene to prepare a mixed solution and the pH value is adjusted to 6-7, the nano-silica is dispersed in the mixed solution, stirred at 110-120° C. for 5-6 hours, cooled to room temperature, filtered, extracted, and dried.

[0018] By adopting the above technical solution, after the nano-silicon dioxide is treated with a silane coupling agent, the compatibility, bonding and dispersibility of the nano-silicon dioxide and the highly flexible polyurethane acrylate are improved, which is conducive to the uniform distribution of the nano-silicon dioxide.

[0019] In the second aspect, the present application provides a method for preparing a new type of ultra-soft PI composite tape, using the following technical solution: A method for preparing a new type of ultra-soft PI composite tape comprises mixing hydroxyl-containing polyimide and highly flexible polyurethane acrylate, adding nano-silicon dioxide and modified graphene oxide, stirring until the mixture is uniform, casting, drying to form a base layer, coating an acrylic adhesive on one side of the base layer, heating and curing, and preparing the PI composite tape.

[0020] By adopting the above technical solution, the prepared PI composite tape has good flexibility and can be bent multiple times without breaking, which greatly reduces the brittle fracture rate.

[0021] In summary, this application has the following beneficial effects: 1. Since the present application adopts a blend of highly flexible polyurethane acrylate and polyimide, the flexibility of the substrate can be effectively improved, thereby improving the flexibility of the PI composite tape, and the addition of nano-silica and modified graphene oxide can improve the mechanical strength of the base layer, so that the PI composite tape has good flexibility while its mechanical properties are not affected. The adhesive layer uses acrylic adhesive, and the hydroxyl group of polyimide has high activity and can be cross-linked with acrylic adhesive and highly flexible polyurethane acrylate, thereby improving the bonding strength between the base layer and the adhesive layer. At the same time, the addition of nano-silica and modified graphene oxide can improve the high temperature resistance of the PI tape, so that the PI composite tape has good heat resistance.

[0022] 2. After the diisocyanate is covalently grafted in the present application, the isocyanate functional group can undergo a cross-linking reaction with the polyurethane, thereby improving the binding property of the modified graphene oxide with the highly flexible polyurethane acrylate, and enabling the graphene oxide to be better dispersed and bonded with the polyimide and the highly flexible polyurethane acrylate, thereby effectively improving the mechanical properties of the composite tape.

[0023] 3. In the present application, after the nano-silica is treated with a silane coupling agent, the compatibility, bonding and dispersibility of the nano-silica and the highly flexible polyurethane acrylate are conducive to the uniform distribution of the nano-silica. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments. Preparation Example 1-11 of Modified Graphene Oxide

[0025] Preparation Example 1 The modified graphene oxide is diisocyanate covalently grafted graphene oxide. The preparation method of diisocyanate covalently grafted graphene oxide comprises the following steps: ultrasonically dispersing 105 mg of graphene oxide in 30 mL of N, N-dimethylformamide to obtain a graphene oxide suspension, mixing 4'4-diphenylmethane diisocyanate and 18 mL of N, N-dimethylformamide, wherein the mass ratio of graphene oxide to 4'4-diphenylmethane diisocyanate is 0.18:7.89, heating to 55°C with magnetic stirring, dripping the graphene oxide suspension, and dripping 1.5 mL of dibutyltin dilaurate, reacting at 55°C for 8.5 hours, centrifuging, washing, and drying at 50°C for 5 hours to obtain diisocyanate covalently grafted graphene oxide, namely the modified graphene oxide.

[0026] Preparation Example 2 The modified graphene oxide is diisocyanate covalently grafted graphene oxide. The preparation method of diisocyanate covalently grafted graphene oxide comprises the following steps: ultrasonically dispersing 95 mg of graphene oxide in 25 mL of N, N-dimethylformamide to obtain a graphene oxide suspension, mixing 4'4-diphenylmethane diisocyanate and 15 mL of N, N-dimethylformamide, wherein the mass ratio of graphene oxide to 4'4-diphenylmethane diisocyanate is 0.12:7.69, heating to 55°C with magnetic stirring, dripping the graphene oxide suspension, and dripping 2 mL of dibutyltin dilaurate, reacting at 55°C for 8 hours, centrifuging, washing, and drying at 50°C for 5 hours to obtain diisocyanate covalently grafted graphene oxide, namely the modified graphene oxide.

[0027] Preparation Example 3 The modified graphene oxide is diisocyanate covalently grafted graphene oxide. The preparation method of diisocyanate covalently grafted graphene oxide comprises the following steps: ultrasonically dispersing 118 mg of graphene oxide in 33 mL of N, N-dimethylformamide to obtain a graphene oxide suspension, mixing 4'4-diphenylmethane diisocyanate and 20 mL of N, N-dimethylformamide, wherein the mass ratio of graphene oxide to 4'4-diphenylmethane diisocyanate is 0.24:8.26, heating to 55°C with magnetic stirring, dripping the graphene oxide suspension, and dripping 2 mL of dibutyltin dilaurate, reacting at 55°C for 9 hours, centrifuging, washing, and drying at 55°C for 4 hours to obtain diisocyanate covalently grafted graphene oxide, namely the modified graphene oxide.

[0028] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that in Preparation Example 4, the mass ratio of graphene oxide to 4'4-diphenylmethane diisocyanate is 0.18:5.64.

[0029] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the mass ratio of graphene oxide to 4'4-diphenylmethane diisocyanate is 0.18:9.52.

[0030] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 1 is that in Preparation Example 6, the modified graphene oxide is also treated as follows: 4.8 mL of styrene is stirred and dissolved in 50 mL of anhydrous ethanol, 0.5 g of modified graphene oxide is added and ultrasonically fractionated, 0.09 g of benzoyl peroxide is added, heated in a water bath at 50° C. and stirred for 10 min, reacted at 80° C. for 6 h, cooled to room temperature, centrifuged, separated, washed with toluene, and vacuum dried.

[0031] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 1 is that in Preparation Example 7, the modified graphene oxide is also treated as follows: 5.5 mL of styrene is stirred and dissolved in 50 mL of anhydrous ethanol, 0.6 g of modified graphene oxide is added and ultrasonically fractionated, 0.11 g of benzoyl peroxide is added, heated in a water bath at 55° C. and stirred for 8 min, reacted at 85° C. for 5.5 h, cooled to room temperature, centrifuged, separated, washed with toluene, and vacuum dried.

[0032] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 6 is that in Preparation Example 8, the amount of styrene added is 3 mL.

[0033] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 6 is that in Preparation Example 9, the amount of styrene added is 7 mL.

[0034] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 6 is that in Preparation Example 10, the modified graphene oxide is further treated as follows before being dispersed in the anhydrous ethanol solution of styrene: 38 mg of modified graphene oxide is ultrasonically dispersed in 20 mL of water to obtain a modified graphene oxide suspension, 1 mL of silane coupling agent KH-550 is stirred and dissolved in 60 mL of anhydrous ethanol, added to the modified graphene oxide suspension, and ultrasonically dispersed, the pH is adjusted to 4, the temperature is raised to 50°C for reaction for 3.5 hours, the temperature is raised to 70°C for reaction for 3.5 hours, and after cooling to room temperature, centrifugation, separation, anhydrous ethanol washing, and vacuum drying.

[0035] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 6 is that in Preparation Example 11, the modified graphene oxide is further treated as follows before being dispersed in the anhydrous ethanol solution of styrene: 43 mg of modified graphene oxide is ultrasonically dispersed in 25 mL of water to obtain a modified graphene oxide suspension, 1.2 mL of silane coupling agent KH-550 is stirred and dissolved in 65 mL of anhydrous ethanol, added to the modified graphene oxide suspension, and ultrasonically dispersed, the pH is adjusted to 5, the temperature is raised to 55°C for reaction for 3 hours, the temperature is raised to 75°C for reaction for 3 hours, and after cooling to room temperature, centrifugation, separation, anhydrous ethanol washing, and vacuum drying. Preparation Example of Hydroxyl-Containing Polyimide

[0036] Preparation Example 12 0.44 mol of p-hydroxybenzaldehyde, 0.15 mol of aniline and 2.58 mmol of aniline hydrochloride were mixed, nitrogen was introduced, the temperature was raised to 110°C, stirred and mixed, the temperature was raised to 150°C and reacted for 2 hours, cooled to room temperature, 10 wt% hydrochloric acid was added to dissolve, sodium hydroxide solution was added to adjust the pH to 9, the aqueous phase was washed with ether to remove aniline, filtered, dried at 50°C for 12 hours, separated by column chromatography, a mixed solution of chloroform, ethyl acetate and methanol in a volume ratio of 80:18:2 was selected as the eluent, and the solvent was removed by reduced pressure distillation under nitrogen protection to obtain diamino-hydroxytriphenylmethane; 1.5 mmol of diamino-hydroxytriphenylmethane was dissolved in 5 mL of N-methylpyrrolidone, 1.5 mmol of hexafluorodianhydride was added, and after stirring for 3 hours, 10 mL of N-methylpyrrolidone was added, and 200 mL of a mixture of methanol and water in a volume ratio of 1:1 was added, filtered, vacuum dried at 50°C for 12 hours, dispersed in xylene, refluxed for dehydration for 90 minutes, filtered, washed with n-hexane, and vacuum dried at 50°C for 12 hours to obtain a hydroxyl-containing polyimide.

[0037] Preparation Example of Highly Flexible Polyurethane Acrylate Preparation Example 13 2 mol of polybutene diol was heated to 120°C, dehydrated under reduced pressure for 2 hours, cooled to 50°C, 4 mol of toluene diisocyanate was added, heated to 70°C, reacted for 4 hours, 4.3 mol of hydroxyethyl acrylate was added, and 5.9 g of p-hydroxyanisole, 0.6 g of hydroquinone and 0.5 mL of dibutyltin dilaurate were added, heated to 80°C, reacted for 3 hours, and highly flexible polyurethane acrylate was obtained. Example 1 A new type of ultra-soft PI composite tape comprises a base layer and an adhesive layer, wherein the base layer comprises the following raw materials in parts by weight: 75 kg of hydroxyl-containing polyimide, 20 kg of highly flexible polyurethane acrylate, 6 kg of nano-silicon dioxide, and 2 kg of modified graphene oxide; the adhesive layer is an acrylic adhesive; the hydroxyl-containing polyimide is selected from the hydroxyl-containing polyimide prepared in Preparation Example 12, the highly flexible polyurethane acrylate is selected from the highly flexible polyurethane acrylate prepared in Preparation Example 13, the modified graphene oxide is selected from the modified graphene oxide prepared in Preparation Example 1, and the acrylic adhesive is Henkel 8020‌.

[0039] The preparation method of the above-mentioned ultra-soft new PI composite tape comprises the following steps: mixing hydroxyl-containing polyimide and highly flexible polyurethane acrylate, adding nano-silicon dioxide and modified graphene oxide, stirring until the mixture is uniform, casting, drying at 170°C to form a base layer, irradiating the base layer with an ultraviolet lamp with an ultraviolet dose of 600MJ / cm², coating an acrylic adhesive on one side of the base layer, heating and curing, and obtaining the PI composite tape.

[0040] Example 2 A new type of ultra-soft PI composite tape comprises a base layer and an adhesive layer, wherein the base layer comprises the following raw materials in parts by weight: 67 kg of hydroxyl-containing polyimide, 15 kg of highly flexible polyurethane acrylate, 5 kg of nano-silicon dioxide, and 1 kg of modified graphene oxide; the adhesive layer is an acrylic adhesive; the hydroxyl-containing polyimide is selected from the hydroxyl-containing polyimide prepared in Preparation Example 12, the highly flexible polyurethane acrylate is selected from the highly flexible polyurethane acrylate prepared in Preparation Example 13, the modified graphene oxide is selected from the modified graphene oxide prepared in Preparation Example 2, and the acrylic adhesive is Henkel 8097.

[0041] The preparation method of the above-mentioned ultra-soft new PI composite tape comprises the following steps: mixing hydroxyl-containing polyimide and highly flexible polyurethane acrylate, adding nano-silicon dioxide and modified graphene oxide, stirring until the mixture is uniform, casting, drying at 150°C to form a base layer, irradiating the base layer with an ultraviolet lamp with an ultraviolet dose of 500MJ / cm², coating an acrylic adhesive on one side of the base layer, heating and curing, and obtaining a PI composite tape.

[0042] Example 3 A new type of ultra-soft PI composite tape comprises a base layer and an adhesive layer, wherein the base layer comprises the following raw materials in parts by weight: 85 kg of hydroxyl-containing polyimide, 26 kg of highly flexible polyurethane acrylate, 8 kg of nano-silicon dioxide, and 4 kg of modified graphene oxide; the adhesive layer is an acrylic adhesive; the hydroxyl-containing polyimide is selected from the hydroxyl-containing polyimide prepared in Preparation Example 12, the highly flexible polyurethane acrylate is selected from the highly flexible polyurethane acrylate prepared in Preparation Example 13, the modified graphene oxide is selected from the modified graphene oxide prepared in Preparation Example 3, and the acrylic adhesive is Henkel 8020.

[0043] The preparation method of the above-mentioned ultra-soft new PI composite tape comprises the following steps: mixing hydroxyl-containing polyimide and highly flexible polyurethane acrylate, adding nano-silicon dioxide and modified graphene oxide, stirring until the mixture is uniform, casting, drying at 180°C to form a base layer, irradiating the base layer with an ultraviolet lamp with an ultraviolet dose of 600MJ / cm², coating an acrylic adhesive on one side of the base layer, heating and curing, and obtaining the PI composite tape.

[0044] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 4.

[0045] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 5.

[0046] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 6.

[0047] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 7.

[0048] Example 8 The difference between Example 8 and Example 1 is that in Example 8, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 8.

[0049] Example 9 The difference between Example 9 and Example 1 is that in Example 9, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 9.

[0050] Example 10 The difference between Example 10 and Example 1 is that in Example 10, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 10.

[0051] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 11.

[0052] Example 12 The difference between Example 12 and Example 1 is that in Example 12, the nano-silica is treated as follows: 2 mL of silane coupling agent KH-570 is added to 25 mL of toluene to prepare a mixed solution and the pH value is adjusted to 6, 0.8 g of nano-silica is dispersed in the mixed solution, stirred at 110° C. for 6 hours, cooled to room temperature, filtered, extracted, and dried.

[0053] Embodiment 13 The difference between Example 13 and Example 1 is that in Example 13, the nano-silica is treated as follows: 3 mL of silane coupling agent KH-570 is added to 30 mL of toluene to prepare a mixed solution and the pH value is adjusted to 7, 1.2 g of nano-silica is dispersed in the mixed solution, stirred at 120° C. for 5 h, cooled to room temperature, filtered, extracted, and dried. Comparative Example

[0054] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the base layer includes the following raw materials in parts by weight: 67 kg of hydroxyl-containing polyimide, 10 kg of highly flexible polyurethane acrylate, 12 kg of nano-silicon dioxide, and 3 kg of modified graphene oxide, and the adhesive layer is an acrylic adhesive, and the selection of each raw material is the same as that in Example 1.

[0055] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the base layer includes the following raw materials in parts by weight: 67 kg of hydroxyl-containing polyimide, 30 kg of highly flexible polyurethane acrylate, 2 kg of nano-silicon dioxide, and 7 kg of modified graphene oxide, and the adhesive layer is an acrylic adhesive, and the selection of each raw material is the same as that in Example 1.

[0056] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, no highly flexible polyurethane acrylate is added.

[0057] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, no modified graphene oxide is added. Detection Methods

[0058] According to the raw materials and preparation methods of Examples 1-13 and Comparative Examples 1-4, PI composite tapes were prepared, and the elongation and breaking rate of the PI composite tapes were tested using an EINSTRON-1185 universal material testing instrument. The bending resistance of the PI composite tapes at 25°C was tested using a QY-1 low-temperature bending instrument, and the results are recorded in Table 1.

[0059] Table 1 Performance test of PI composite tape project Elongation at break / % Bending resistance / time (25℃) Example 1 138 ≥60000 Example 2 136 ≥60000 Example 3 135 ≥60000 Example 4 123 ≥50000 Example 5 121 ≥50000 Example 6 159 ≥65000 Example 7 162 ≥65000 Example 8 128 ≥45000 Example 9 126 ≥45000 Example 10 154 ≥65000 Embodiment 11 158 ≥65000 Example 12 146 ≥62000 Embodiment 13 143 ≥63000 Comparative Example 1 116 ≤42000 Comparative Example 2 104 ≤35000 Comparative Example 3 76 ≤15000 Comparative Example 4 62 ≤10000 It can be seen from Examples 1-3, Comparative Examples 1-4 and Table 1 that the PI composite tape prepared in Examples 1-3 has good bending resistance and high elongation at break, indicating that the PI composite tape has good flexibility and strength and good durability. In Examples 1-3, hydroxyl-containing polyimide, highly flexible polyurethane acrylate, nano-silica and modified graphene oxide are added as the base layer of the PI composite tape. The addition of nano-silica and modified graphene oxide can effectively improve the high temperature resistance of the PI composite tape. At the same time, nano-silica and modified graphene oxide have a reinforcing effect, which can effectively improve the mechanical strength and mechanical properties of the PI composite tape, so that the PI composite tape has good flexibility and good durability. Hydroxyl groups are introduced into polyimide to improve the reaction activity, so that the polyimide is cross-linked with the acrylic adhesive and the highly flexible polyurethane acrylate, thereby improving the bonding strength inside the base layer and between the base layer and the adhesive layer, so that the high temperature resistance, flexibility and durability of the PI composite tape are greatly improved.

[0060] Compared with Example 1-3, the bending resistance and elongation at break of Comparative Example 1-2 are both reduced. In Comparative Example 1-2, the mass ratio of the raw materials in the base layer of the PI composite tape is changed, indicating that there is a synergistic effect between the raw materials in the base layer. Controlling the added amount can make the fusion, cross-linking and other reactions between the raw materials proceed smoothly, and the reaction product has good flexibility, strength and durability.

[0061] Compared with Examples 1-3, the bending resistance and elongation at break of Comparative Examples 3-4 are reduced. No highly flexible polyurethane acrylate is added in Comparative Example 3, and no modified graphene oxide is added in Comparative Example 4, indicating that the addition of highly flexible polyurethane acrylate and modified graphene oxide can effectively improve the mechanical properties, flexibility and durability of the PI composite tape.

[0062] Compared with Example 1-3, the bending resistance and elongation at break of Example 4-5 are both reduced. When preparing the modified graphene oxide used in Example 4-5, the mass ratio of graphene oxide to 4'4-diphenylmethane diisocyanate is changed. The mass ratio of graphene oxide to 4'4-diphenylmethane diisocyanate affects the grafting of diisocyanate on the surface of graphene oxide. When the mass ratio is increased, the grafting rate of isocyanate functional groups decreases, so that the content of isocyanate functional groups on the surface of the modified graphene oxide decreases, and the degree of bonding between the modified graphene oxide and the highly flexible polyurethane acrylate is reduced. When the mass ratio decreases, the content of isocyanate functional groups increases, and the degree of cross-linking increases, so that the rigidity of the PI composite tape is enhanced, thereby reducing its flexibility and durability.

[0063] Compared with Examples 1-3, the bending resistance and elongation at break of Examples 6-7 are improved. The modified graphene oxide used in Examples 6-7 has been coated with styrene, and styrene is polymerized on the surface of the modified graphene oxide to form a styrene layer, thereby effectively improving the dispersibility of the modified graphene oxide when mixed with hydroxyl-containing polyimide and high-flexible polyurethane acrylate, which is beneficial to the reinforcing effect of the modified graphene oxide on the PI composite tape.

[0064] Compared with Examples 6-7, the bending resistance and elongation at break of Examples 8-9 are reduced. In Examples 8-9, the amount of styrene added is adjusted. The amount of styrene added directly affects the coating of the modified graphene oxide by styrene. When the amount of styrene added is too little, the coating integrity of the styrene layer is reduced, thereby reducing the dispersibility of the modified graphene oxide. When the amount of styrene added is too much, the coating uniformity of the styrene layer is reduced, making the styrene layer prone to damage and falling off during the subsequent processing of the modified graphene oxide, thereby reducing the dispersibility of the modified graphene oxide.

[0065] Compared with Examples 6-7, the bending resistance and elongation at break of Examples 10-11 are improved. The modified graphene oxide used in Examples 10-11 is also treated with a silane coupling agent before being coated with styrene. After the modified graphene oxide is surface-treated with the silane coupling agent, the dispersibility of the modified graphene oxide in the styrene solution is improved, the grafting of styrene on the surface of the modified graphene oxide is increased, and the dispersibility of the modified graphene oxide is further improved.

[0066] Compared with Examples 1-3, the bending resistance and elongation at break of Examples 12-13 are improved. The nano-silica in Examples 12-13 has been surface treated. After the nano-silica is treated with a silane coupling agent, its dispersibility is improved, and its compatibility with highly flexible polyurethane acrylate and hydroxyl-containing polyimide is improved, which is conducive to the uniform distribution of the nano-silica. At the same time, the composite effect of the nano-silica and modified graphene oxide is improved, and the flexibility of the PI composite tape is jointly improved.

[0067] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A new type of ultra-soft PI composite tape, characterized by: The invention comprises a base layer and a glue layer, wherein the base layer comprises the following raw materials in parts by weight: 67-85 parts of hydroxyl-containing polyimide, 15-26 parts of highly flexible polyurethane acrylate, 5-8 parts of nano silicon dioxide, and 1-4 parts of modified graphene oxide, and the glue layer is an acrylic adhesive.

2. The ultra-soft new PI composite tape according to claim 1, characterized in that: The modified graphene oxide is graphene oxide covalently grafted with diisocyanate.

3. The ultra-soft new PI composite tape according to claim 2, characterized in that: The preparation method of diisocyanate covalently grafted graphene oxide comprises the following steps: ultrasonically dispersing graphene oxide in N,N-dimethylformamide to obtain a graphene oxide suspension, mixing 4'4-diphenylmethane diisocyanate and N,N-dimethylformamide and heating to 55° C. with magnetic stirring, then dripping the graphene oxide suspension and dibutyltin dilaurate, reacting at 55° C. for 8-9 hours, centrifuging, washing, and drying at 50-55° C. for 4-5 hours to obtain diisocyanate covalently grafted graphene oxide.

4. The ultra-soft new PI composite tape according to claim 3, characterized in that: The mass ratio of the graphene oxide to 4'4-diphenylmethane diisocyanate is (0.12-0.24):(7.69-8.26).

5. The ultra-soft new PI composite tape according to claim 1, characterized in that: The modified graphene oxide is also treated as follows: styrene is stirred and dissolved in anhydrous ethanol, the modified graphene oxide is added and ultrasonically fractionated, benzoyl peroxide is added, heated in a water bath at 50-55° C. and stirred for 8-10 minutes, reacted at 80-85° C. for 5.5-6 hours, cooled to room temperature, centrifuged, separated, washed with toluene, and vacuum dried.

6. The ultra-soft novel PI composite tape according to claim 5, characterized in that: Before being dispersed in the anhydrous ethanol solution of styrene, the modified graphene oxide is further subjected to the following treatments: ultrasonically dispersing the modified graphene oxide in water to obtain a modified graphene oxide suspension, stirring and dissolving a silane coupling agent in anhydrous ethanol, adding the agent to the modified graphene oxide suspension and ultrasonically dispersing the agent, adjusting the pH to 4-5, heating the agent to 50-55° C. for reaction for 3-3.5 hours, heating the agent to 70-75° C. for reaction for 3-3.5 hours, cooling the agent to room temperature, centrifuging, separating, washing with anhydrous ethanol, and vacuum drying the agent.

7. The ultra-soft novel PI composite tape according to claim 1, characterized in that: The nano silicon dioxide is treated as follows: adding silane coupling agent into toluene to prepare a mixed solution and adjusting the pH value to 6-7, dispersing the nano silicon dioxide in the mixed solution, stirring at 110-120° C. for 5-6 hours, cooling to room temperature, filtering, extracting and drying.

8. The method for preparing the new ultra-soft PI composite tape according to any one of claims 1 to 7, characterized in that: The following steps are involved: The hydroxyl-containing polyimide and high-flexible polyurethane acrylate are mixed, nano-silicon dioxide and modified graphene oxide are added, stirred until the mixture is uniform, and then cast into a film. After drying at 150-180°C, a base layer is formed. The base layer is irradiated with a UV lamp with a UV dose of 400-600MJ / cm². Acrylic adhesive is coated on one side of the base layer, and the temperature is increased to cure to obtain a PI composite tape.